A Single Nucleotide C3 Polymorphism Associates With Clinical Outcome After Lung Transplantation - Kardol-Hoefnagel, Tineke; Budding, Kevin; van de Graaf, Eduard A.; van Setten, Jessica; van Rossum, Oliver A.; Oudijk, Erik-Jan D.; Otten, Henderikus G. (Frontiers in Immunology, 2019)
Abstract Background: Development of chronic rejection is still a severe problem and causes high mortality rates after lung transplantation (LTx). Complement activation is important in the development of acute rejection (AR) and bronchiolitis obliterans syndrome, with C3 as a key complement factor. Methods: We investigated a single nucleotide polymorphism (SNP) in the C3 gene (rs2230199) in relation to long-term outcome after LTx in 144 patient-donor pairs. In addition, we looked at local production of donor C3 by analyzing bronchoalveolar lavage fluid (BALF) of 6 LTx patients using isoelectric focusing (IEF). Results: We demonstrated the presence of C3 in BALF and showed that this is produced by the donor lung based on the genotype of SNP rs2230199. We also analyzed donor and patient SNP configurations and observed a significant association between the SNP configuration in patients and episodes of AR during 4-years follow-up. Survival analysis showed a lower AR-free survival in homozygous C3 slow patients (p=0.005). Furthermore, we found a significant association between the SNP configuration in donors and BOS development. Patients receiving a graft from a donor with at least one C3 fast variant for rs2230199 had an inferior BOS-free survival (p=0.044). Conclusions: In conclusion, our data indicate local C3 production by donor lung cells. In addition, a single C3 SNP present in recipients affects short-term outcome after LTx, while this SNP in donors has an opposite effect on long-term outcome after LTx. These results could contribute to an improved risk stratification after transplantation.